Comprehensive evaluation of low-temperature properties of PPA/CR/SBS composite modified asphalt binder and its mixtures - Fucheng Guo; Ning Li; Songbai Lin; Bo Li; Zhenzheng Liu; Yongning Wang; Sheng Guo; Jing Zhao; Wenzhou Li (Results in Engineering)
Asphalt pavement in cold regions often suffer from serious cracking issues, which will greatly shorten its service life. Composite modification employing polyphosphoric acid (PPA), crumb rubber (CR), and styrene-butadiene-styrene block copolymer (SBS) offers an eco-friendly approach to enhancing low-temperature performance of asphalt binders. This study evaluated the low-temperature properties of various PPA/CR/SBS composite asphalt binder using bending beam rheometer (BBR) testing for binder and semi-circular bending (SCB) test for mixture. Moreover, the comprehensive evaluation was carried out using entropy weight-TOPSIS method. Results indicate that all composite-modified binders outperform SBS-modified asphalt binder in low-temperature rheological properties. Activated crumb rubber (ACR) markedly decreases the risk of low-temperature cracking, whereas PPA addition enhances performance but slightly increases the cracking risk. Fracture energy Gf exhibits stability and strong correlation (r > 0.83) with rheological indices. Notably, ACR/SBS-P demonstrates the best low-temperature performance among five types of composite binders evaluated.